Evaluation of mechanical properties of sustainable and eco-friendly ultra-high-performance concrete using ternary cementitious binders (Advances in Civil and Architectural Engineering, 2024)
Building structures using Ultra-High Performance Concrete (UHPC) with better mechanical and durability properties requires effort and consideration for the environment. The present study comprises 17 distinct trial mixes or UHPC. The cementitious content ranges from 1200-1400 kg/m3, the water-to-cementitious ratio varies from 0,16-0,18, and micro-steel fibres measuring 0,2 × 13,0 mm are included at a proportion of 1,5 % of the total concrete volume. A variety of ingredients including cement, fly ash, micro-silica, fine sand, high-range water reducer, shrinkage reducing admixture, micro-steel fibres and water were utilised. Specimens were cast and evaluated at 7, 14, and 28 days for mechanical properties such as flexural, indirect tensile, and compressive strength, as well as fresh concrete characteristics, such as the slump cone test. The results indicate that there was an improvement in the slump cone value as the fly ash content increased. The mechanical characteristics were enhanced by the increase in micro-silica, which is attributed to the refining of the pore structure and the pozzolanic reactivity during the early stages. Optimal blend ratio for maximizing the compressive, tensile and flexural strength of UHPC has been identified in mixes where 15-20 % of cement has been replaced by Supplementary Cementitious Materials (SCMs) in various combinations. The replacement ratio was found to enhanced mechanical properties due to optimized particle packing and improved matrix density within the concrete.